2021
DOI: 10.1155/2021/6614331
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value and Potential Mechanism of miRNA-33a-5p in Lung Squamous Cell Carcinoma

Abstract: This study is aimed at thoroughly exploring the expression status, clinical significance, and underlying molecular mechanism of miRNA-33a-5p in lung squamous cell carcinoma (LUSC). Here, we detected miRNA-33a-5p in 20 samples from patients with LUSCs and 20 matching non-LUSC specimens by in-house quantitative real-time PCR (RT-qPCR). Relationship between miRNA-33a-5p expression and clinicopathological traits was investigated from materials derived from miRNA sequencing and miRNA microarrays. A pool standard me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Tang et al reported that MNDA expression was lower in lung adenocarcinoma, and this response correlated with the upregulation of has-miR-33a-5p [ 40 ]. Furthermore, Wang et al showed that hsa-miR-33a-5p was overexpressed in lung squamous cell carcinoma tissues compared with that in normal lungs, thus playing an essential role in the onset and development of the disease [ 55 ]. Consistent with these data, we observed a significant increase in hsa-miR-33a-5p in the LC group and the COPD group with respect to healthy ones, thus providing evidence of cancer-like dysregulation in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al reported that MNDA expression was lower in lung adenocarcinoma, and this response correlated with the upregulation of has-miR-33a-5p [ 40 ]. Furthermore, Wang et al showed that hsa-miR-33a-5p was overexpressed in lung squamous cell carcinoma tissues compared with that in normal lungs, thus playing an essential role in the onset and development of the disease [ 55 ]. Consistent with these data, we observed a significant increase in hsa-miR-33a-5p in the LC group and the COPD group with respect to healthy ones, thus providing evidence of cancer-like dysregulation in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA-33a-5p is an intron miRNA that is located inside the intron sequence of the sterol-response-element-binding protein gene 2 (SREBP2) ( 63 ). The study has shown that miR-33a-5p promotes apoptosis via targeting nodal modulator1 (NOMO1) and other targets ( 64 ).…”
Section: Role Of Mirna In Cmec In Cardiovascular Diseasementioning
confidence: 99%